Odpowiedzi

Najlepsza Odpowiedź!
2010-02-06T13:46:23+01:00
0,12*3/4-(3/5-2,1*5/7)=12/10*3/4-(3/5-21/10*5/7)=9/10-(3/5-3/2)=9/10-(-9/10)=9/10+9/10=18/10=1,8

-1,2:0,3* (-2/5)=-4*(-2/5)=8/5=1 i 3/5

√4²+√3² ×1/5+ ( -3/4)²=4+3x1/5+9/16=4+4,5+9=17,5
2 3 2
2010-02-06T13:53:48+01:00
0,12×3÷4-(3/5-2,1×5/7) -1,2: 0,3×(-2/5)×√4²+√3² ×1/5+ (-3/4)²=0,9-(0,6-1,4994)-1,2÷(-0,12)×4+3×0,2=0,9+0,8994+10*4+0,6= 1,7994+40,6=42,3994

mam nadzieję, że pomogłam :)
1 5 1
2010-02-06T14:01:15+01:00
0,12*3/4-(3/5-2,1*5/7)=12/100*3/4-(3/5-21/10*5/7)=12/100*3/4-(3/5-3/2)=12/100*3/4-(6/10-15/10)=12/100*3/4+9/10=9/100+90/100=99/100

-1,2:0,3* (-2/5)=-4*(-2/5)=(-4/1)*(-2/5)=8/5=1 3/5

√4²+√3² ×1/5+ ( -3/4)²=4+3*1/5+(-9/16)=4/1+3/5-9/16=320/80+48/80-45/80=323/80=4 3/80